Chilean journalistic texts in the Independence period - Ayala Pérez, Teresa (Boletín de Filología, 2010)
The press is the oldest mass media there is, and although at presentthe technologies have changed the medium in which these texts arepublished or how they reach readers, the journalistic discourse hascertain features that allow us to know something of the society inwhich it occurs and, because of this, are a reflection of the societyin a certain moment. For this reason, and on the occasion of theBicentennial of Chile, it is pertinent to go back to the beginnings of thepress in our country and try to approach the period of independencethrough the journalistic texts published in la Aurora de Chile and ElMonitor Araucano, the first newspapers in our country, through adiscursive approach, with special attention to the context and referentsof the daily life of the young country.